Labor Market Frictions and Spillover Effects from Publicly Announced Sectoral Minimum Wages - Gökay Demir (Institute of Labor Economics (IZA), 2023)
This paper analyzes the spillover effects of the first sectoral minimum wage in Germany. Using a triple differences estimation, the study examines the impact of public discussion and announcement of the minimum wage on workers and industries outside the minimum wage sector. The results show that the public discussion and announcement led to an increase in wages, job-to-job transitions and reallocation from low-paying to high-paying establishments among sub-minimum wage workers in similar jobs outside the minimum wage sector. The main mechanism for these effects appears to be the reduction of information frictions, rather than strategic interaction of employers.
Keywords: J31; J38; J42; J62; 330; spillover; labor market frictions; minimum wages; information frictions